Governance in entrepreneurial ecosystems: Venture capitalists vs. technology parks - Douglas Cumming; Jochen Christian Werth; Yelin Zhang (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
We argue two alternative routes that lead entrepreneurial start-ups to acquisition outcomes instead of liquidation. On one hand, acquisitions can come about through the control route with external financers such as venture capitalists (VCs). VCs take control through their board seats along with other contractual rights that can bring about changes in a start-up necessary to successfully attract a strategic acquirer. Consistent with this view, we show that VCs often replace the founding entrepreneur as CEO long before an acquisition exit. On the other hand, acquisitions can come about through advice and support provided to the start-up, such as that provided by an incubator or technology park. Based on a sample of 251 Crunchbase companies in the U.S. over the years 2007 to 2014, we present evidence that is strongly consistent with these propositions. Further, we show that the data indicate a tension between VC-backing of start-ups resident in technology parks insofar as such start-ups are slower to become, and less likely to be, acquired.
urn:nbn:de:hebis:30:3-400673
Keywords: G23; G24; L26; 330; Entrepreneurship; Entrepreneurial Finance; Governance; Technology Park; Incubator; Board of Directors; Venture Capital; Angel